The Role of Income Audit in Internal Control of Food and Beverage Revenue at Hotel XY - Putu Sahra DIVANDA; Anak Agung Istri M. SEPTIVIARI; Christina SUSANTI (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the role of Income Audit in strengthening internal control of food and beverage revenue at XY Hotel and examine its relationship with the COSO internal control framework. This study uses qualitative and quantitative approaches with data obtained from primary sources, namely job descriptions and standard operating procedures for Income Audit and also secondary data in the form of interviews and documentation involving Income Audit, Chief Accountant and Restaurant Bar Cashier. Data analysis uses the Miles and Huberman model consisting of data reduction, data presentation and conclusion drawing. The research findings reveal that the implementation of COSO components significantly affects the effectiveness of Income Audit in the revenue cycle, especially in handling transaction processes, as well as in information systems that cause delays in document collection. These results indicate that improvements are needed in document management and control procedures to align with COSO standards and increase the reliability of Income Audit in supporting effective financial governance.